Pengaruh Bahan Amelioran Sekam Padi dan Serbuk Gergaji terhadap Stabilitas Agregat, Kadar Air dan C-Organik Tanah serta Pertumbuhan Tanaman Nilam pada Tanah Bekas Tambang - Berlian, Citra; Ginting, Sahta; Leomo, Sitti; Darwis, Darwis; Rembon, Fransiscus S.; Namria, Namria (CV. Eduartpia Publisher, 2023)
Soil sampling was carried out at PT. Wijaya Inti Nusantara, Torobulu Village, Laeya District, South Konawe Regency.This study used a randomized block design (RBD) consisting of 7 treatments, namely: B0D0 = without amelioran, B1DI = ameliorant of rice husk 50g/polybag, B1D2 = ameliorant of rise husk 100g/polybag, B1D3 = ameliorant of rice husk 150g/polybag, B2D1 = ameliorant of sawdust 50 g/polybag, B2D2 = ameliorant of sawdust 100 g/polybag , and B2D3 = Amelioran sawdust 150 g/polybag, each treatment was repeated 3 times and 21 research units were obtained.The results of the study on the effect of ameliorants on the growth of patchouli plants in ex-mining soil showed that the highest treatment was C-organic B2D3 3.38% (T), water content B1D3 34.5% week 4, and aggregate stability B1D1, B1D2 , B1D3 (3) Total Slanging.The effect of using ameliorant on the growth of patchouli plants in ex-mining soil has an effect on plant height and biomass variables compared to no treatment. The best results were found in the B2D3 treatment.Keywords: ameliorant, patchouli, rice husk, sawdust